INSPEKSI KESELAMATAN JALAN DI JALAN LINGKAR SELATAN YOGYAKARTA - Supradian Sujanto; Agus Taufik Mulyono (Jurnal Transportasi, 2010)
Traffic accident causes economic losses for the country, the victim, and the victim’s family. The cause of traffic accident consists of human error, vehicle factor, and road and environment factor. Human error is mostly considered as the main reason for traffic accidents to occur. This Study is intended to find the road safety deficiency in Ring Road Selatan Yogyakarta, from Parangtritis Road intersection (STA 0+000) to Bantul Road intersection (STA 1+600), using road safety form developed by Directorate General of Highways. Any kind of deviation from technical standard and dangerous condition of environment will be compared with the rules which prevails. The deviencies found will be presented in accident opportunity value (P) and seriousness of victim’s condition impact value (D). The correlation between opportunity and impact values will result in risk value (R) that indicates road safety condition. The average of risk value in Ring Road Selatan Yogyakarta is 74,10 which means that the risk value is low or the safety deviciency level is small. Zone with the highest risk value is zone 4 (STA 0+400) with 114,40, which can be categorized as medium level meaning that this zone needs unscheduled handling. The routine road treatment for road pavement, road mark, traffic sign, and street illumination can reduce risk value from 74,10 to 43,33, meaning that the road can be categorized as very low level of handling and does not need to be monitored.Keywords: road safety deficiency, road safety form, and risk value